What's a Girl to Do?: The Pleasures and Pressures of the Girls' Night Out. Issue 3 (1st December 2021) - Unknown
Abstract : Nicholls, Emily. 2019. Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl? London: Palgrave Macmillan.